2018 International Atmospheric Rivers Conference: Multi‐disciplinary studies and high‐impact applications of atmospheric rivers. (26th July 2019) - Ramos, Alexandre M.; Wilson, Anna M.; DeFlorio, Michael J.; Warner, Michael D.; Barnes, Elizabeth; Garreaud, Rene; Gorodetskaya, Irina V.; Lavers, David A.; Moore, Benjamin; Payne, Ashley; Smallcomb, Chris; Sodemann, Harald; et al.
Abstract: Atmospheric rivers (ARs) play a vital role in shaping the hydroclimate of many regions globally, and can substantially impact water resource management, emergency response planning, and other socioeconomic entities. The second International Atmospheric Rivers Conference took place at the Scripps Institution of Oceanography, University of California, San Diego, during 25–28 June, 2018, in La Jolla, California, USA. It was sponsored by the Center for Western Weather and Water Extremes (CW3E). A total of 120 people attended the Conference with 94 abstracts submitted and 30 participating students. In addition to the conference, the Student Forecasting Workshop was organised in the same week. During this workshop, students were exposed to AR forecasting tools, and learned examples of how these tools could be used to make decisions for various applications. The main goals of this conference were to bring together experts from across the fields of hydrology, atmospheric, oceanic, and polar sciences, as well as water management, civil engineering, and ecology to advance the state of AR science and to explore the future directions for the field. The conference was organised into traditional oral and poster presentations, along with panel discussions and Breakout Groups. This format allowed enhanced interaction between participants, driving progress within the scientific community and the enhanced communication of societal needs by various stakeholders. Several emerging topics of research were highlighted, including subseasonal‐to‐seasonal (S2S) prediction of ARs and an overview of the AR Reconnaissance campaign. In addition to providing a forum to disseminate and debate new results from scientific talks and posters, the conference was equally effective and useful in linking scientists to users and decision‐makers that require improved knowledge on ARs to manage resources and prepare for hazards. The third International Atmospheric Rivers Conference will be held in Chile in 2020, and hosted by the University of Chile, Santiago. Abstract :